A new species of Mycomya Rondani (Diptera, Mycetophilidae, Mycomyinae) from Argentinean Patagonia - Omad, Guillermo; Pessacq, Pablo; Anjos-Santos, Danielle (Zootaxa, 2017)
Mycomya bowiei n. sp. is described based on male and female specimens from Argentinean Patagonia. Additionally, we provide a redescription of Mycomya bifida Freman (1951) and new records of three species of Mycomya previously unrecorded from either Chubut Province or Argentina.